STUDI DESKRIPTIF PEMBELAJARAN DARING MATA PELAJARAN PPKn PADA SISWA KELAS VIII SMP NEGERI 2 MOJOSONGO KABUPATEN BOYOLALI DI MASA PANDEMI COVID-19 TAHUN PELAJARAN 2021/2022 - Joned Eko Prasetyo; Sudiyo Widodo Sudiyo (LPPM Universitas Widya Dharma, 2022)
The outbreak of the Corona virus in early 2020 made the world stop for a moment from the hectic daily activities. The COVID-19 virus, as determined by the World Health Organization, was upgraded from an epidemic to a pandemic. The purpose of this study was to determine the application of online learning for Civics subjects to class VIII students used at SMP Negeri 2 Mojosongo, Boyolali Regency during the pandemic, to determine the level of student participation in online learning. To find out the advantages, weaknesses, and obstacles of online learning during a pandemic, to find out student learning outcomes by implementing online learning for Civics subjects during a pandemic. The research was conducted using data collection methods with interviews and documentation. Data validation used the Norman K. Denkin triangulation method. Results of online learning research are generally carried out using information technology and not only for communication, but also used as a learning medium during the pandemic. Online learning is carried out with the help of the parents of each student at home. The role of teachers with limitations that exist during the current covid-19 pandemic is trying to provide material to the maximum, even though with full effort. The role of the homeroom teacher is also important, as the homeroom teacher must also know how the situation of each student in the class even though they cannot meet face-to-face.